2021
DOI: 10.1088/1748-605x/ac1f9f
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of chitosan/graphene oxide nanocomposite coatings on Mg–2 wt% Zn scaffold by pulse electrodeposition process

Abstract: Mg and its alloys are biodegradable and mechanically strong materials, which can be used for an orthopedic implant and device applications, but corrosion rate of these alloys is high. In this research, the nanocomposite coatings of chitosan (CS)/graphene oxide (GO) were fabricated to improve the corrosion resistance of the Mg–2 wt% Zn scaffold. The contents of the GO nanosheets and the pulse electrodeposition process parameters, including peak current density (CD) and duty cycle (DC), will also be investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 60 publications
(75 reference statements)
0
9
0
Order By: Relevance
“…Different techniques are applied to the development of three-dimensional composite scaffolds of chitosan-CNM like freeze-drying and thermally induced phase separation (TIPS) for biomedical implant applications. Some of these synthesis techniques have been used for these mentioned compositions by a number of a researcher like electrodeposition for biomedical implant applications, 3D printing for biomedical application and production possibility of the antimicrobial filaments, freeze-drying for antimicrobial activity, and covalent crosslinking for bone tissue engineering [ 103 , 104 , 105 , 106 , 107 ].…”
Section: Synthesis Techniques Of Chitosan Compositesmentioning
confidence: 99%
“…Different techniques are applied to the development of three-dimensional composite scaffolds of chitosan-CNM like freeze-drying and thermally induced phase separation (TIPS) for biomedical implant applications. Some of these synthesis techniques have been used for these mentioned compositions by a number of a researcher like electrodeposition for biomedical implant applications, 3D printing for biomedical application and production possibility of the antimicrobial filaments, freeze-drying for antimicrobial activity, and covalent crosslinking for bone tissue engineering [ 103 , 104 , 105 , 106 , 107 ].…”
Section: Synthesis Techniques Of Chitosan Compositesmentioning
confidence: 99%
“…The porous nanostructure significantly affected the wettability to obtain a superhydrophobic surface with a higher contact angle. Hamghavandi et al (2021) studied the effect of PED process parameters and the composition of nanocomposite coating with chitosan and graphene oxide on the Mg-Zn scaffold with a porosity closer to that of bone. The best performance was obtained for a composition of chitosan with 2 wt.% GO when coated using a current density of 20 mA/cm 2 and a duty cycle of 0.5.…”
Section: Electrodepositionmentioning
confidence: 99%
“…The study conducted by Seyedraoufi et al aimed to examine the PED method on the characteristics of nHA covering on the with a 2% weight of Zn and scaffold, with the ultimate goal of evaluating its suitability for use in the bone tissues 33 . The experimental findings by Hamghavandi et al 34 indicated that the optimal factors to synthesize a CS/GO coating on the Mg scaffolds were 2% weight GO, j = 20 mA/cm 2 , and a duty cycle of 0.5. Notably, limited research has been carried out regarding enhancing the resistance to corrosion and biological compatibility of nHA/CS coating on the Mg‐2Zn scaffold by employing the PED technique.…”
Section: Introductionmentioning
confidence: 99%